Approximation of Periodic Functions of High Smoothness by Interpolation Trigonometric Polynomials in the Metric of $L_1$ - Serdyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We establish an asymptotically exact estimate for the error of approximation of ℝ2-periodic functions of high smoothness by interpolation trigonometric polynomials in the metric of L 1.